THE EVOLUTIONARY IDEAS OF F. M. (LADIMIR) KLACEL, TEACHER OF GREGOR MENDEL - Peaslee, Margaret H.; Orel, Vitezslav (Biomedical papers, 2007)
Abstract: A philosopher and teacher, F. M. (Ladimir) Klacel (1808-1882), educated in what is now the Czech Republic, developed his own explanation for the origin and interaction of living organisms. Klacel, a member of the Augustinian Monastery in Brno, infl uenced his younger colleague, Friar Gregor Mendel, who went on to formulate concepts in heredity that are still recognized for their profound insight. A mutual interest in the natural sciences of these two friends provided a basis for their discussions of the relationship between religion, evolution, and society. Klacel's outspoken defense of his proposals caused him to lose favor with both the Church and the authorities, and he immigrated to America in 1869. His failing health and inability to communicate with the English-speaking populace, unfortunately, limited his infl uence in his new environs. In this paper we trace the roots of Klacel's philosophy and elucidate his incorporation of ideas from Hegel, Darwin, and others. An investigation of Klacel's recipe for a successful society reveals his belief in the universality of life and his optimistic hope for human achievement.
Keywords: Breeding methods/Heredity/Natural science/Physiology/Philosophy